Chronodisruption and Obesity - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Indonesian Biomedical Journal, 2015)
BACKGROUND: Attempts to understand the causes of obesity and develop new therapeutic strategies have mostly focused on caloric intake and energy expenditure. Recent studies have shown that the circadian clock controls energy homeostasis by regulating circadian expression and/or activity of enzymes, hormones, and transport systems involved in metabolism. Moreover, disruption of circadian rhythms leads to obesity and metabolic disorders.CONTENT:Regularly alternating periods of light and darkness, such as normally occur with the rising and the setting of the sun, are essential for the maintenance of undisturbed circadian rhythms in all organisms including humans. The light-dark environment, as detected by specialized photoreceptors in the retinas, impacts the endogenous circadian clock in the anterior hypothalamus, the suprachiasmatic nuclei. These nuclei, via both neural and humoral signals, communicate with cells throughout the organism to establish regular circadian rhythms. The introduction of artificial sources of light roughly 150 years ago has significantly undermined the naturally occurring light-dark environment and, likewise, has disturbed circadian rhythms since light is now available at unusual times, i.e., at night. Light at night is known to cause circadian disruption and melatonin suppression. Many potentially pathophysiological consequences of these artificial light-mediated changes, include cancer, cardiovascular diseases, insomnia, metabolic syndrome, diabetes, and cognitive disorders may be aggravated by the increased exposure to light at night, which is inevitable in well-developed societies that have undergone extensive electrification.SUMMARY: Therefore, it is plausible that resetting of the circadian clock can be used as a new approach to attenuate obesity. Feeding regimens, such as restricted feeding, calorie restriction and intermittent fasting, provide a time cue and reset the circadian clock and lead to better health. In contrast, high-fat diet leads to disrupted circadian expression of metabolic factors and obesity.KEYWORDS: obesity, circadian clock, metabolism, chronodisruption